MODERN TEACHING REQUIREMENTS OF THE SUBJECT “INFORMATION TECHNOLOGY IN MEDICINE” (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article analyzes modern approaches, digital tools, and interactive teaching methods in the instruction of the subject “Information Technology in Medicine.” The role of information technologies in medical education, their importance in effectively organizing the learning process, and their contribution to developing students’ information literacy and digital competencies are highlighted. Technological possibilities such as modular teaching, distance learning, simulation programs, and the use of clinical databases are also analyzed.